PEDAGOGICAL ASPECTS OF PREPARING GIRLS FOR FAMILY LIFE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the pedagogical aspects of preparing girls for independent family life. It emphasises the importance of creative cooperation between the family and the community in teaching girls practical skills related to organising family life, managing household relationships, and running domestic affairs. The study highlights the role of Uzbekistan’s state policy in strengthening families, promoting social and educational support, and creating conditions for the holistic development of young women. The article analyses the principles, methods, and experiences of successful collaboration among families, educational institutions, public organisations, and state agencies in preparing girls for family life.